2021
DOI: 10.1007/s00405-021-06737-1
|View full text |Cite
|
Sign up to set email alerts
|

UV light-based reprocessing of flexible endoscopes without working channel in Oto-Rhino-Laryngology: an effective method?

Abstract: Background Reprocessing of flexible endoscopes (FEs) is often expensive, time consuming, and becomes increasingly complex, due to rising demands of hygiene. After beneficial results in reprocessing of rigid endoscopes using Impelux™ UV-C light technology, we tested the same method for reprocessing of FEs without working channel. Materials and methods Testing was performed on FEs without working channel after routine clinical use (transnasal flexible endosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 20 publications
(20 reference statements)
1
13
3
Order By: Relevance
“…Furthermore, almost all endoscopes were sterile and almost protein-free after reprocessing, which fulfils the regulatory requirements for "high-level" disinfection [ 18 ]. Similar results were found for flexible endoscopes without a working channel using the same technology [ 19 ]. Furthermore, the virucidal properties of the disinfection system tested here have already been investigated, which is particularly important in the current COVID 19 pandemic.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, almost all endoscopes were sterile and almost protein-free after reprocessing, which fulfils the regulatory requirements for "high-level" disinfection [ 18 ]. Similar results were found for flexible endoscopes without a working channel using the same technology [ 19 ]. Furthermore, the virucidal properties of the disinfection system tested here have already been investigated, which is particularly important in the current COVID 19 pandemic.…”
Section: Introductionsupporting
confidence: 82%
“…With correspondingly positioned test bodies, the light system achieved an absolute germ reduction of 6 log levels and was thus able to fulfil the requirements of the legislator for the reprocessing of semi-critical medical devices, tested so far. In another UV light-based disinfection system of the Dutch company UV Smart, similar results were achieved in the reprocessing of flexible ENT endoscopes without working channel [ 19 ]. After use on a patient, the flexible endoscopes showed an average contamination of 916.7 CFU with potentially pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…UV-C radiation causes the dimerization of thymine in DNA and uracil in RNA in the irradiated microorganisms as well as RNA-protein cross-links, which leads to an inactivation [ 18 , 19 ]. In previous studies, the device tested here showed satisfactory results in terms of bactericidal efficacy for ORL-endoscopes [ 14 , 20 ]. The tested UV system was developed for the disinfection of rigid ORL-endoscopes ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 65%
“…Although some UV-C disinfection companies claim to offer this, no definite proof of HLD with UV-C systems was found in literature. There are studies reporting up to 7-log reductions for artificially contaminated flexible endoscopes [ 48 ]. However, they often do not take the risk of genomic repair into account or have a conflict of interest.…”
Section: Resultsmentioning
confidence: 99%